ANALISIS STRATEGI PENGEMBANGAN USAHA PETERNAKAN AYAM PEDAGING BROILER DI DESA SAING RAMBI KECAMATAN SAMBAS - Farita, Veren; Nashirun; Gustina (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This research was motivated by the unstable development of broiler farming in Saing Rambi Village, Sambas District. This is caused by some broiler breeders having insufficient skills in raising broiler chickens, there are also other factors that hinder chicken farming in Saing Rambi Village, such as poor water supply. However, if the strategy for raising broiler chickens can be applied well, this broiler farming business can provide quite high profits because it is quite popular with the public and many people consume chicken. This research aims to determine strategies that can be applied in developing broiler chicken farming businesses in Saing Rambi Village, Sambas Regency using SWOT analysis. The method used by researchers is qualitative and the data collection techniques used are observation, interviews and documentation. The research setting was in Saing Rambi Village, Sambas Regency. The primary data source is 10 broiler breeder owners in Saing Rambi Village, Sambas Regency. Where the data analysis techniques used are data reduction, data display, and drawing conclusions and the data validity techniques used are triangulation and member checking. The results of the research can be concluded that the strategy for dealing with business development is to increase knowledge about managing broiler chicken farms, especially in controlling diseases and pests in chickens. Apart from that, what needs to be improved is competitive marketing procedures so that it can increase the amount of profit per period.